MiR-668-5p targets ZNRF3, an E3 ubiquitin ligase to enhance osteoblast function and alleviate senescence in doxorubicin-induced age-related bone loss - Singh, Devendra Pratap; Tripathi, Alok; Paul, Ankita; Kaushal, Saurabh Kumar; Dixit, Megha; Singh, Divya (Frontiers in Endocrinology, 2025)
IntroductionAging is a complex biological phenomenon that drives the progression of numerous chronic conditions, including osteoporosis, which is characterized by bone loss and increased risk of fragility fractures. The study of microRNA (miRNA) functions has provided valuable insights into the mechanisms that regulate aging and the senescence process. In this study, we identified microRNA 668-5p (miR-668-5p) as a novel regulator of osteoblast function and further elucidated its role in age-related bone loss driven by cellular senescence.MethodsmiR-668-5p function was assessed through mimic transfection in osteoblasts, with osteogenic differentiation evaluated by osteogenic gene and protein expression. Target confirmation was conducted using a dual luciferase 3′UTR reporter assay to identify Znrf3, an E3 ubiquitin ligase and negative regulator of Wnt signaling, as a direct target of miR-668-5p. Cellular senescence was induced using doxorubicin (Doxo), a well-established agent for simulating an accelerated aging phenotype. Further, the effects of miR-668-5p on senescence markers (SA-β-gal activity, p53, p21), reactive oxygen species (ROS) levels, and Znrf3 expression were examined. In vivo, miR-668-5p was administered to Doxo-treated mice, and trabecular bone microarchitecture was evaluated using microCT, while bone regeneration and bone strength were analyzed using calcein incorporation and mechanical testing, respectively.ResultsTransfection with the miR-668-5p mimic enhanced osteoblast differentiation and function, as indicated by increased expression of osteogenic markers. Znrf3 was confirmed as a direct target, mediating the regulation of Wnt signaling. Doxo treatment suppressed miR-668-5p expression, increased Znrf3 levels, and promoted cellular senescence and ROS. miR-668-5p augmentation mitigated these effects, reducing senescence markers and ROS production. In vivo, miR-668-5p administration improved trabecular bone microarchitecture, bone regeneration, and bone strength in Doxo-treated mice. Notably, Znrf3 overexpression in osteoblasts reversed the anti-senescence and pro-osteogenic effects of miR-668-5p, confirming its target-specific role.DiscussionThese findings establish miR-668-5p as a key regulator of osteoblast function and bone homeostasis through its direct targeting of Znrf3 and modulation of Wnt signaling. By alleviating senescence and promoting osteogenesis, miR-668-5p demonstrates therapeutic potential in combating age-related bone loss and osteoporosis.